2018
DOI: 10.1021/acs.biomac.8b00295
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-State NMR Analysis of Nanocelluloses

Abstract: Recent developments in ionic liquid electrolytes for cellulose or biomass dissolution has also allowed for high-resolution H andC NMR on very high molecular weight cellulose. This permits the development of advanced liquid-state quantitative NMR methods for characterization of unsubstituted and low degree of substitution celluloses, for example, surface-modified nanocelluloses, which are insoluble in all molecular solvents. As such, we present the use of the tetrabutylphosphonium acetate ([P][OAc]):DMSO- d ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 68 publications
1
94
0
7
Order By: Relevance
“…Therefore, it is necessary to apply suitable analytical methods to monitor the removal of the IL. In this case, the CNFF chemical compositions were assessed using FTIR, as a rapid technique and a novel liquid-state NMR method involving the dissolution of the films into IL electrolyte solution 49 , and XRD measurements. Figure 2 shows the FTIR spectra of the untreated and IL welded sample.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Therefore, it is necessary to apply suitable analytical methods to monitor the removal of the IL. In this case, the CNFF chemical compositions were assessed using FTIR, as a rapid technique and a novel liquid-state NMR method involving the dissolution of the films into IL electrolyte solution 49 , and XRD measurements. Figure 2 shows the FTIR spectra of the untreated and IL welded sample.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Increasing the water content in the cellulose sample further to higher numbers (20 wt% and 30 wt% of water) than the equilibrated moisture content of 7 wt%, did not significantly influence the kinetics of the reactions ( Figure S3) but reduced the degree of substitution (DS) of the acetylated fibers and hence the reaction efficiency (Table S2). Our results, based on diffusion-edited 1 H-NMR spectra of the acetylated fibers ( Figure 3A) in the ionic liquid [P4444][OAc] 40 (more details can be found in Supplemental Methods 1.8 and Figure S4), showed that that smaller amounts of secondary hydroxyl groups were modified under these conditions, i.e., increasing selectivity for the primary 6-OH.…”
Section: Figurementioning
confidence: 76%
“…When a diffusion-edited 1 H experiment for the same sample is measured, compared to the standard 1 H experiment ( Figure A9), it is clear to see that there is polymeric material in the DMSO-d6 solution. Diffusion-editing has the effect of removal of the low molecular weight resonances and retention of the polymeric resonances [68]. The retained signals in the soluble organic fraction from the FUR:isophorone reaction correspond to both polymerised FUR and isophorone.…”
Section: Effect Of Reaction Timementioning
confidence: 99%